Konsep Pendidikan Islam Syeikh Az-Zarnuji (Telaah Filsafat Islam) - author; Aminah (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2013)
This study discusses the concept of Islamic education Shaykh Az-Zarnuji, the study of philosophy of education. In the specific issues to be discussed here is how the concept of Islamic education by Sheikh Az-Zarnuji contained in his book titled Ta’lim al-Muta’allim that reveal the basic principles of Islamic education. To achieve understanding of the concept of Islamic education Shaykh Az-Zarnuji, the approach used by the educational philosophy of the primary data source book Ta’lim al-Muta’allim, while data sekundemya using educational materials about Islam, especially that there relefansinya the problems faced. Results of this study indicate that Sheikh Az-Zarnuji thinking about Islamic education is the emphasis on the basic principles of Islamic education yung has three basic distinctive character, the Godhead, Individuality and Community (humanity). Education is the importance of understanding the implications of the values of religious ethics, where science thing (religion) occupy the highest place.